2019
DOI: 10.1038/s41598-019-54760-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of neuronal ensemble activity reveals the pitfalls and shortcomings of rotation dynamics

Abstract: Back in 2012, Churchland and his colleagues proposed that “rotational dynamics”, uncovered through linear transformations of multidimensional neuronal data, represent a fundamental type of neuronal population processing in a variety of organisms, from the isolated leech central nervous system to the primate motor cortex. Here, we evaluated this claim using Churchland’s own data and simple simulations of neuronal responses. We observed that rotational patterns occurred in neuronal populations when (1) there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 50 publications
(50 reference statements)
5
62
0
Order By: Relevance
“…Figure 2 in Churchland, Cunningham et al (2012) indeed illustrates ten neurons (selected from the data of four monkeys) whose responses are variable across conditions. Yet, we have already shown that, at population level, a consistent sequence of neuronal responses is present in Churchland's data (see Figure 2 in Lebedev, Ossadtchi et al (2019)). To examine this finding further, here we ranked the neurons in Churchland's population by how consistent the timing of their responses was across the conditions.…”
Section: Responses With Consistent Timingsupporting
confidence: 64%
See 4 more Smart Citations
“…Figure 2 in Churchland, Cunningham et al (2012) indeed illustrates ten neurons (selected from the data of four monkeys) whose responses are variable across conditions. Yet, we have already shown that, at population level, a consistent sequence of neuronal responses is present in Churchland's data (see Figure 2 in Lebedev, Ossadtchi et al (2019)). To examine this finding further, here we ranked the neurons in Churchland's population by how consistent the timing of their responses was across the conditions.…”
Section: Responses With Consistent Timingsupporting
confidence: 64%
“…With this simple procedure, we found a temporal sequence of neuronal responses during the arm reaching task. This sequence persisted across 108 conditions with some variability (see Figure 2 in Lebedev, Ossadtchi et al (2019)). Based on this observation, we argued that sequence-like responses could be the cause of the rotational dynamics revealed with jPCA.…”
Section: ̇=mentioning
confidence: 91%
See 3 more Smart Citations